1979
DOI: 10.3758/bf03335000
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative contrast effects as a function of shifts in percentage of reward

Abstract: Two experiments examined the effects of shifts in reward percentage on acquisition of an instrumental running response. In Experiment 1, a group shifted from 33% reward to 100% reward ran faster following the shift than did a group that received 100% reward throughout training; that is, a positive contrast effect was observed. In Experiment 2, animals shifted from 100% to 33% reward exhibited a negative contrast effect; that is, they ran slower following the shift than did control animals that received 33% rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…All five papers that included the proper controls found evidence of a SucNCE when schedules were made leaner (Dyck et al, 1977;Fox, 1972; McHose & Peters, 1975;Seybert, 1979). In the McCain et al study, the NCE occurred only on the third shift in a LSLS sequence of shifts.…”
Section: Shifts In Schedule Of Rewardmentioning
confidence: 99%
See 2 more Smart Citations
“…All five papers that included the proper controls found evidence of a SucNCE when schedules were made leaner (Dyck et al, 1977;Fox, 1972; McHose & Peters, 1975;Seybert, 1979). In the McCain et al study, the NCE occurred only on the third shift in a LSLS sequence of shifts.…”
Section: Shifts In Schedule Of Rewardmentioning
confidence: 99%
“…For example, SucPCEs should be long lasting. This sometimes happens (e.g., Mellgren, 1971aMellgren, , 1973Seybert, 1979),but sometimes does not (e.g., McHose & Moore, 1978;Premack & Hillix, 1962;Seybert & Mellgren, 1971). McHose and Moore, whose paper was designed to compare the magnitude and the duration of both contrasts, found them similar in magnitude and SucPCEs to be of relatively short duration.…”
Section: Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, subjects that are shifted from a larger to a smaller reward in a runway run slower following the shift than subjects that always receive a smaller reward (Flaherty, 1982). Although most of these studies shifted the amount of reward to produce the contrast effect, some studies (Fox, 1972;Seybert, 1979) showed the contrast effect by shifting the amount of effort to obtain a reward, as in studies on the work-ethic effect discussed here.The deteriorated performance is attributed to frustration that is produced by a less attractive reward compared to an anticipated reward or by demanding more effort to obtain a reward (Amsel, 1958; see also Amsel, 1992;Bower, 1961). Previous studies have shown that the negative contrast effect was widely evidenced in rats (Crespi, 1942;Seybert, 1979;Vogel, Mikulka, & Spear, 1968) and even human infants (Kobre & Lipsitt, 1972); however, extensive studies have failed to obtain the negative contrast effect in pigeons (Papini, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…The deteriorated performance is attributed to frustration that is produced by a less attractive reward compared to an anticipated reward or by demanding more effort to obtain a reward (Amsel, 1958; see also Amsel, 1992; Bower, 1961). Previous studies have shown that the negative contrast effect was widely evidenced in rats (Crespi, 1942; Seybert, 1979; Vogel, Mikulka, & Spear, 1968) and even human infants (Kobre & Lipsitt, 1972); however, extensive studies have failed to obtain the negative contrast effect in pigeons (Papini, 1997). From this viewpoint, monkeys in the present experiment would experience frustration with the FR20‐schedule (high‐effort) when they had obtained a reward by low‐effort (i.e.…”
Section: Discussionmentioning
confidence: 99%